2020
DOI: 10.1089/chi.2020.0183
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Gestational Diabetes and Early Childhood Obesity: A Retrospective Cohort Study

Abstract: Background: Recently, childhood obesity has become one of the most serious public health problems in the world. Gestational diabetes mellitus (GDM) is considered a risk factor for childhood overweight and obesity. The study aimed at investigating the relationship between maternal GDM and childhood obesity in children aged from 1 to 3 years. Methods: In this retrospective cohort study, 237 GDM and 296 non-GDM mothers and their offspring who were followed up by Family Medicine Clinics in Rize province of Turkey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…Furthermore, a novel survey by Choi et al [ 40 ] is in line with our findings, as the authors observed that maternal obesity before gestation and GDM further raise the probability of childhood obesity at 5 years [ 40 ]. Another recent retrospective study by Ardic et al [ 41 ] also found that GDM increases the probability for childhood obesity at the ages of 2 and 3 years old.…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, a novel survey by Choi et al [ 40 ] is in line with our findings, as the authors observed that maternal obesity before gestation and GDM further raise the probability of childhood obesity at 5 years [ 40 ]. Another recent retrospective study by Ardic et al [ 41 ] also found that GDM increases the probability for childhood obesity at the ages of 2 and 3 years old.…”
Section: Discussionmentioning
confidence: 92%
“…These findings align with doctors' observations, which are in complete accordance with the extensive scientific research in this field. Various studies have conclusively established that gestational diabetes is a significant risk factor for the subsequent development of obesity in young children[ 20 , 21 ]. In addition, a review by Adriana Mannino and colleagues concluded that the impact of maternal overweight on childhood obesity is no longer open to dispute, underlining the need for targeted interventions to prevent this growing scourge[ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite these limitations, there is consistent evidence of an association between maternal diabetes and child obesity, described in diverse populations including from China [ 13 ], Denmark [ 14 ], Sweden [ 15 ], Turkey [ 16 ], South Korea [ 17 ] and in the multi-ethnic Hyperglycemia and Adverse Pregnancy Outcomes (HAPO) cohort [ 10 ]. There is also emerging evidence of a dose-dependent effect of maternal hyperglycaemia upon offspring obesity, with risk increasing proportionately with maternal glucose concentrations in pre-gestational and gestational diabetes [ 11 , 14 ].…”
Section: Childhood Obesity After Diabetes In Pregnancy: the Scale Of ...mentioning
confidence: 99%